Answer: Option D.
Step-by-step explanation:
Given the quadratic equation [tex]3x^2+8x=-1[/tex], you can observe that the leading coefficient is not 1, then you have to divide both sides of the equation by 3:
[tex]\frac{3x^2+8x}{3}=\frac{-1}{3}\\\\x^2+\frac{8}{3}x=\frac{-1}{3}[/tex]
Now, you can observe that the coefficient of the x-term is [tex]\frac{3}{8}[/tex], so you must divide it by 2 and square it. Then you get:
[tex](\frac{\frac{8}{3}}{\frac{2}{1}})^2=\frac{16}{9}[/tex]
Therefore, you must add [tex]\frac{16}{9}[/tex] to both sides of the equation.